PERFORMANCE OF FP 200 PVDF MEMBRANE EQUIPMENT IN POLYPHENOL PURIFICATION FROM PINK GUAVA JUICE WASTE - Sukeksi, Lilis; Hassan, Che R.C.; Sulaiman, Nik M.N. (Universitas Medan Area, 2019)
Juice processing plants, such as pink guava, still contain substances that have economic value such as anti-oxidant polyphenols. The polyphenols recovery process is carried out using a membrane separation FP 200 PVDF type, by reason of the membrane separation process without using heat to avoid damage from the polyphenols structure. The duration of the recovery process affects the performance of flow rate of the membrane, there is a decrease in the flow rate of 0.033 ml/min for the process in TMP 1 bar and 0.038 ml/min and 0.044 ml/min for TMP 2 and 3 bars respectively. Cleaning is done to improve membrane performance, cleaning using HNO3 is more effective than just using clean water. The process of recovery of polyphenols was carried out at 1 bar TMP and resulting 54% recovery of polyphenols. After the cleaning process % recovery of polyphenols decreases compared to the results of the first recovery. SEM shows the absorption of polyphenols and other contaminants in the pores of the membrane, thus affecting the performance of the membrane